Where Two 'Exceptional' Prison Cultures Meet: Negotiating Order in a Transnational Prison. (14th August 2020) - Liebling, Alison; Johnsen, Berit; Schmidt, Bethany E; Rokkan, Tore; Beyens, Kristel; Boone, Miranda; Kox, Mieke; Vanhouche, An-Sofie
Abstract: Can a prison in the Netherlands, that is neither 'Dutch' nor 'Norwegian', be 'legitimate?' What are the moral challenges? Our study of the controversial Norgerhaven project—a Norwegian prison located in the Netherlands—found that this 'experiment' generated one of the most reflexive, 'deliberative' prisons we have encountered. Officials involved in the decision assumed that the two jurisdictions were alike in their values. Few were prepared for the differences that arose. This hybrid prison made punishment, the use of authority, and the meanings of fairness, professionalism and discipline unusually explicit as staff negotiated their practices, creating a shift from 'practical' to 'discursive' consciousness and exposing many of the complexities of liberal penal power.